Analisis Kualitas Layanan Kesehatan untuk Narapidana dengan Diabetes Mellitus di Lapas Kelas IIA Kendari - Razikin Rahman (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2025)
The background of this study derives from the importance of fulfilling the right to adequate healthcare services for all citizens, including prisoners within correctional facilities. At Lembaga Pemasyarakatan Kelas IIA Kendari, although diabetes cases are not predominant, mortality data indicate that complications arising from this disease are among the leading causes of death. This study aims to evaluate the quality of healthcare services provided to inmates with diabetes mellitus and to identify the obstacles encountered in their implementation. This research employed a descriptive qualitative method, utilizing in-depth interviews, direct observations, and documentation studies involving diabetic inmates and medical staff at the prison clinic. The findings reveal that the overall quality of healthcare services is moderately good, with notable variations across dimensions based on L.D. Brown’s theoretical framework. The dimensions of accessibility and interpersonal relations stand out as the strongest aspects, reaching the very good category due to the clinic’s strategic location, free healthcare services, 24-hour emergency availability, and the friendly, empathetic, and non-discriminatory interactions of medical personnel that foster patient trust and adherence. The dimensions of safety, comfort, information, and timeliness are rated as good, supported by strict isolation protocols, a clean and inclusive clinical environment, clear health education delivery, and prompt responses to emergency situations. However, the dimensions of technical competence, effectiveness, efficiency, and continuity remain suboptimal. This is mainly due to limited ongoing training for medical personnel, failure to prevent fatal complications, reliance on external referrals caused by resource constraints, and administrative barriers that delay elective referral processes. The key challenges identified include limited medical infrastructure, such as the absence of laboratory facilities and diagnostic equipment, insufficient operational budgets, and bureaucratic procedures that hinder timely access to specialist healthcare outside the prison.